2008
DOI: 10.5194/hess-12-101-2008
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological responses of a watershed to historical land use evolution and future land use scenarios under climate change conditions

Abstract: Abstract. Watershed runoff is closely related to land use but this influence is difficult to quantify. This study focused on the Chaudière River watershed (Québec, Canada) and had two objectives: (i) to quantify the influence of historical agricultural land use evolution on watershed runoff; and (ii) to assess the effect of future land use evolution scenarios under climate change conditions (CC). To achieve this, we used the integrated modeling system GIBSI. Past land use evolution was constructed using satell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 30 publications
(26 reference statements)
0
30
0
Order By: Relevance
“…Thus, effective water resources management now needs to take account of, and understand, the interactions between land use change, climate change and hydrological responses. It has been suggested that the use of a hydrological model which is conceptualized to accurately represent hydrological processes, sensitive to land use and adequately accounts for climate change drivers provides a means of assessing these complex interactions (Turner et al, 1995;Ewen and Parkin, 1996;Bronstert et al, 2002;Herron et al, 2002;Chang, 2003;Pfister et al, 2004;Hu et al, 2005;Samaniego and Bárdossy, 2006;Lin et al, 2007;Choi and Deal, 2008;Guo et al, 2008;Quilbé et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, effective water resources management now needs to take account of, and understand, the interactions between land use change, climate change and hydrological responses. It has been suggested that the use of a hydrological model which is conceptualized to accurately represent hydrological processes, sensitive to land use and adequately accounts for climate change drivers provides a means of assessing these complex interactions (Turner et al, 1995;Ewen and Parkin, 1996;Bronstert et al, 2002;Herron et al, 2002;Chang, 2003;Pfister et al, 2004;Hu et al, 2005;Samaniego and Bárdossy, 2006;Lin et al, 2007;Choi and Deal, 2008;Guo et al, 2008;Quilbé et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in annual runoff was also detected following tree felling (Robinson and Dupeyrat, 2005) accompanied by an increase in low flows. While impacts of land cover change are more likely to be evident in small catchments, Quilbé et al (2008) found that the hydrological regime of a 6682 km 2 catchment was sensitive to changes between agricultural land and shrub over a 30-year period and Siriwardena et al (2006) report an increase of 40% in annual runoff following substantial forest clearance of a large catchment (16,440 km 2 ). Paired catchment studies are also a standard method for investigating how land cover (particularly grass and forest) affects runoff (e.g.…”
Section: Effect Of Change In Land Covermentioning
confidence: 99%
“…One purpose has been simulating impacts of change, for example, climate and land cover, on the flow regime but models are often run with the assumption that rainfall-runoff processes in the current or baseline time period are applicable under the changed conditions (e.g. Quilbé et al, 2008;Prudhomme et al, 2013). Many models require catchment-specific calibration of model parameters through optimising fit between observed and simulated flow over a particular period of data, but increasingly research has allowed models to be set-up through development of generalised relationships between physical catchment properties and model parameter values which can be applied over national or larger areas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Quilbé et al (2008), it is unrealistic to model land use projections for a period of more than 20 to 30 years. A short-term prediction window allows the construction of realistic scenarios, particularly concerning agricultural practices.…”
Section: Future Land Usementioning
confidence: 99%
“…This unexpected result emerged for moderate changes in climate for the short-term horizon (2025) compared to the reference period. The choice of such a shortterm timescale was related to the difficulty of adequately predicting land use changes for time scales of more than 20-30 years, as stated by Quilbé et al (2008). Nevertheless, we wanted to test the hypothesis that at a longer time scale and with increased warming, the effects of climate change on water quality outputs could reach the magnitude of land use impact.…”
Section: Impacts Of Land Use Change On Water Qualitymentioning
confidence: 99%